Analysis of the Effect of Corporate Social Responsibility on Company Management Performance: Analisis Pengaruh Corporate Social Responsibility terhadap Kinerja Manajemen Perusahaan - Zakiah, Mahira Ilmi; Harianto, Wiwit (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: Corporate Social Responsibility (CSR) significantly influences company performance in today’s business environment. Specific Background: Inconsistent findings exist regarding CSR's impact on management performance, particularly in Indonesia’s state-owned enterprises (BUMN). Knowledge Gap: This study addresses this gap by examining the effects of environmentally and socially oriented CSR on the management performance of BUMN companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022. Aims: The study aims to empirically assess how CSR influences management performance using quantitative data from annual reports. Results: The findings reveal that both environmentally and socially oriented CSR positively impact management performance, with implications for financial outcomes. Novelty: This research offers new insights into the relationship between CSR initiatives and firm performance. Implications: The results provide valuable information for investors and corporate managers, highlighting the necessity of effective CSR strategies to enhance operational performance and build investor confidence. Highlights: Positive Impact: Both environmentally and socially oriented CSR significantly enhance management performance in BUMN companies. Investment Insights: Effective CSR strategies are essential for building investor confidence and improving financial outcomes. Research Contribution: This study fills the knowledge gap by empirically linking CSR initiatives to firm performance in Indonesia. Keywords: Corporate Social Responsibility, Management Performance, State-Owned Enterprises, Indonesia Stock Exchange, Financial Outcomes